Recent Advances in the Potential of Positive Allosteric Modulators of the GABAB Receptor to Treat Alcohol Use Disorder. (9th February 2021) - Augier, Eric
Abstract: Aims: The effects of alcohol on gamma-aminobutyric acid (GABA) transmission are key for the development and maintenance of alcohol use disorder (AUD). Previous research consistently indicates that GABAB receptor agonists such as baclofen can attenuate addiction-related behaviors in preclinical models of AUD. More importantly, baclofen has also shown promise in clinical studies, particularly in severely alcohol-dependent patients. However, despite this promise, other clinical studies have not confirmed its efficacy and chiefly, larger clinical trials have not been conducted. Therefore, with the exception of France, baclofen is not approved for the treatment of AUD in any other country. Furthermore, it is also important to keep in mind that some patients treated with baclofen may experience important side-effects, including sedation, drowsiness and sleepiness. Methods: This short review will first discuss the history of baclofen for AUD treatment. We will then summarize preclinical behavioral results that have investigated the efficacy of GABAB PAMs for addiction treatment, with a special focus on our recent work that investigated the effects of ADX71441, a novel GABAB PAM, on several alcohol-related behaviors in rats that model important aspects of human AUD. Finally, in light of the recent criticism about the translational value of animal models of addiction, the specific translational potential of our work and of other preclinical studies that have unanimously reported the efficacy of GABAB PAMs to attenuate multiple alcohol-related behaviors will be discussed. Results: Positive allosteric modulators (PAMs) of the GABAB receptor offer an attractive alternative approach to baclofen and have the potential to achieve mechanistic and therapeutic effects similar to GABAB agonists, while avoiding the tolerance and toxicity issues associated with baclofen. To date, all preclinical behavioral results have invariably shown the efficacy of GABAB PAMs for addiction treatment. Conclusions: Preclinical studies indicate that GABAB PAMs have a higher therapeutic index than orthosteric agonists, at least in terms of mitigating the sedative effects of GABAB agonism. This predicts that GABAB PAMs have a high translational potential in humans and merit being tested clinically, in particular in patients with severe AUD. Abstract : Short Summary: Despite promising preclinical and clinical results, baclofen has limitations and is not widely approved for AUD treatment. PAMs were developed as an alternative pharmacological approach to targeting a similar mechanism. This review will discuss the history of baclofen for AUD treatment and focus on the specific translational potential of GABAB PAMs to attenuate multiple alcohol-related behaviors in preclinical studies.